PENGARUH PROMOSI, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KEMBALI PRODUK UMKM - Rahmatika, Annisa; Indiani, Ni Luh Putu (AkMen JURNAL ILMIAH, 2024)
Indonesians have known and used efficacious plants to overcome health problems before modern medicine. This study aims to determine the influence of promotion, brand image, and price on repurchase decision of herbal oil in Bali. The study population is the brand customers in Bali area. The data analysis technique uses multiple linear regression analysis. The results showed that promotion, brand image and price positively and significantly influence repurchase decision. To improve brand image, SME needs to maintain its brand image that is proven to be effective in healing, maintain the image of the product as a traditional medicine that prioritizes natural ingredients and is efficacious for relatively short healing, make products that have distinctive aromas that are different from other products and make products with good quality and can be distinguished from other brands in the same category. To improve the performance of price variables, SME needs to set affordable prices, price according to quality, price according to benefits, and ensure prices are in accordance with consumers’ purchasing power. Aspects that need to be considered to improve promotions are ensuring advertisements attract attention, introducing products in detail, designing effective sales promotions, building good relationships with consumers, and being more aggressive in direct marketing.